Discussion of “An analytical probabilistic analysis of slopes based on limit equilibrium methods” by A. Johari, S. Mousavi. November 2018, DOI: https://doi.org/10.1007/s10064-018-1408-1 - Jamshidi Chenari, Reza; Izadi, Ardavan (Bulletin of engineering geology and the environment, 2019)
The authors, having a long and abiding interest in analytical and numerical approaches to evaluate stability problems such as slope stability analysis in the stochastic soil mechanics discipline incorporating the random field theory, welcome the paper by Johari and Mousavi (Bull Eng Geol Environ 2018:1–15, 2018 ) for their efforts to evaluate the reliability of four different commonly used limit equilibrium method approches for slope stability evaluations, including simplified Bishop, simplified Janbu, Morgenstern-Price, and Spencer. The application of jointly distributed random variables, as an alternative method of Monte-Carlo simulations, in probabilistic analysis with the advantage of approaching more accurate solutions in a lower computational time, a truncated normal probability distribution function, and an optimization procedure with a particle swarm optimization technique, are some appealing aspects of the Johari and Mousavi’s slope stability analyses. However, we would like to point out some considerations which are fundamental for carrying out an analytical probabilistic analysis of slopes based on limit equilibrium.